Unveiling Portal Vein Anatomy: Clinical Impact and Significance of Variants in Transjugular Intrahepatic Portosystemic Shunt Creation - Yancey, Kristina; Ruddy, Liane; Simmons, Curtis L.; Crawford, Daniel A.; Alzubaidi, Sadeer; Naidu, Sailen; Ozen, Merve (Seminars in Interventional Radiology, 2025)
An in-depth understanding of portal venous anatomy, particularly its variants, is essential for interventional radiologists performing complex hepatobiliary procedures such as transjugular intrahepatic portosystemic shunt (TIPS) creation. Anatomical variations in the portal venous system occur in approximately 35% of the population, and failure to identify these variants can result in significant procedural complications including vascular injury and postprocedural liver failure. This article discusses the most common (types I–V) portal vein variants and the importance of their preprocedural identification, their potential impact on procedural outcomes, and the role of advanced imaging techniques in mitigating risks associated with these anatomical variations.
Keywords: portal vein; portal vein anatomy; mesenteric vein; interventional radiology